DETERMINANTS OF EARNING MANAGEMENT IN THE FINANCIAL SECTORS - Priyanto, Ryki Yuni Adi; Irawati, Wiwit (KEUNIS, 2022)
This research aims to provide empirical evidence regarding the effect of deferred tax expense, current tax expense, and asset growth on earnings management. This research was conducted on sub-financial manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. Hypothesis testing was carried out using the EViews 09 application. A sample of companies was selected using a purposive sampling technique using several criteria according to research needs. Based on the test results, it is revealed that deferred tax expense, current tax expense, and asset growth simultaneously significantly affect earnings management. Deferred tax expense and current tax expense variables do not affect earnings management, while asset growth variables affect earnings management.